Back to the Same Place of Holidays. An Analysis of European Tourists’ Preferences Towards Cultural Tourism - Amaral, Rui (2020)
Cultural tourism remains one of European tourists’ main preference for travelling inside Europe (Kozak, 2002; Chaldler&Costello, 2012). The European Commission (EC) estimated that cultural tourism accounts for 40% of all European tourism; 4 out of 10 tourists choose their destination based on cultural attributes and attractions (EC, 2018). Furthermore, travel has long been associated with cultural standards and levels, because a visitor who is motivated to explore, discover and learn about the attractions of a country or region exerts an incalculable personal, social and professional investment. Tourism demand and the study of tourists’ preferences have had a profound effect on the tourist behaviour field of research. In this way, different perspectives can be broadly categorized, such as under a decision-making process of destination, regarding the point of viewof tourism experience and the identification of the components of tourist behaviour (Suh&Gartner, 2004, among others). Particularly, revisit behaviour or repeat visitation is affected by several factors, such as reputation or quality of a particular destination (Alegre&Cladera, 2006; Barros&Assaf, 2012; Perales, 2002, among others). A controversial idea about motivations of cultural tourists was stated by Pulido-Fernández and Sánchez-Rivero (2010), who claimed that these individuals are motivated by novelty, because they are more complex, sophisticated and demand more experience about destinations, prices and availability, motivated by new and unique experiences in the destination.